Microstructural Evolution and Mechanism of Strengthening in Al-Zn/fly ash/ ZrO2 Composites Fabricated Through a Vortex - Swamy, Gari Surya Chandra; Mishra, Himanshu; Kumar P, Jamaleswara (International Journal of Integrated Engineering, 2022)
This paper describes fabrication of aluminium-zinc (Al-Zn) alloy (AZ91E) metal matrix composites augmented with Fly Ash (FA) and zirconium dioxide (ZrO2) particulate utilising the vortex method and a stir casting process. The researchers introduced composites with ZrO2and fly ash at varied weight % ranging from 0 to 10 with 53 µm particle sizes. The inclusion of ZrO2 particle reinforcement increased the hardness significantly, whereas the ultimate yield and tensile strengths increased somewhat. As the weight % of ZrO2 particles was increased, the permeability and density of Al-Zn alloy based composites increasing. Additionally, the compressive and tensile crack properties of the composites produced were investigated. Microstructural analyses confirmed the presence of evenly dispersed FA and ZrO2 particles throughout the matrix, but an EBSD study revealed that this led to diminished reduction. The inclusion of FA particles enhanced the material’s tensile properties and hardness including ultimate yield and tensile strengths. The strengthening mechanisms underlying the enhanced properties were discussed.